Integration in an international university in Malaysia - Sengupta, Enakshi (2015)
Abstract The purpose of the current study is to investigate the relationship between experiences with diversity offered in an international university in Malaysia and the ways students and staff view integration. The problem that promoted this study arose from the researcher’s own experience of being an international student with difficulties in integrating in a multi-cultural environment in the university. Two outcomes are investigated in this study, the meaning of the term ‘integration’ as viewed by the students and staff and the conscious effort that is being implemented by authority and the students themselves towards achieving an optimal level of integration. This research intends to investigate the gap between the ideal level of integration and the existing level, and offer solution towards bridging the gap. Although several studies have been conducted in the past that extol the benefits of being educated in a more racially diverse environment, it is a relatively new area of educational research especially in the South Asian context and in Malaysia. Malaysia is on its way to becoming a hub for international students. The policy-makers in Malaysian higher education realize that with the influx of foreign students comes the issue of integrating these students and faculty that have come from other countries. This study had been designed to bridge the gap that exists between the local and international students and with the local community outside the campus. Findings from the study along with the theories from the literature review present the current scenario on integration and the recommendations suggest a way forward for the institution to reduce inter-group prejudices and foster optimal integration in the campus. The thesis begins with an introduction to the current scenario and summarizes the meaning of the term integration, race and ethnicity and its relevance to the concept of internationalisation as proposed by exponents in this field of research. The thesis then elaborates on the context of the study with the focus on Malaysian Higher Education policies and policies on internationalisation as drafted by the University of Nottingham and the relevance of such policies towards the study. The researcher explores literature found in this field of work and selects three theories to form the foundation of the study. The chapter on the literature review explains the theories in detail and how these three theories have been used to explore the current study. The research methodology is explained with the University of Nottingham Malaysia Campus being chosen as a single case study to help focus attention on the case. A mixed method was used in designing the research, combining both quantitative and qualitative research methods in different ways, where both distinctive approaches contribute towards an understanding of the phenomenon. Quantitative research was conducted with 291 students from various departments in the second and third year of their studies and qualitative interviews were conducted with 15 participants comprising students and members of the teaching and administrative staff. The findings were analysed using SPSS version 20 and NVivo software. The analysis of the quantitative data was further discussed and the data showed that more than half the participants lacked clarity on the meaning of the word integration and its significance in their lives. Students and staff members showed a lack of clarity and understanding of the policies promoted by the university to foster integration. Students preferred being in their homogeneous race groups when it came to their academic activities. They also preferred spending their leisure time with students of their own race. The students were appreciative of the fact that the faculty respects every student equally and tries consciously to mix the races in assignment groups. The study revealed the complexity of the perception-practice dynamic, and the multi-faceted factors which influence student perception and behaviour in relation to optimal integration. Taking the findings from relevant literature and the results of the present study into account, recommendations for the university have been formulated regarding student integration. The recommendations consist of a clear vision and realistic goals in terms of integration. Recommendations also consist of promoting intercultural exchange through inculcating diversity in the curriculum and promoting intercultural interaction between international students and the local community outside the university campus and to carefully monitor integration and react appropriately to changes. The thesis ends with a conclusion summarizing the key findings, the significance of the study, limitations of the study and the scope for future research. The study recommends interventions to be used at different stages to measure and monitor the impact of such interventions towards creating optimal integration in the university and reduce the prejudice prevalent amongst racial groups in the campus at present.